2022
DOI: 10.1029/2021jg006596
|View full text |Cite
|
Sign up to set email alerts
|

Ammonium Sensitivity of Biological Nitrogen Fixation by Anaerobic Diazotrophs in Cultures and Benthic Marine Sediments

Abstract: Biological nitrogen fixation (BNF) is the dominant source of new bioavailable nitrogen (N) in the ocean (Gruber & Galloway, 2008;Zhang et al., 2020). By replenishing fixed N lost by denitrification and anammox, BNF promotes N availability and marine productivity. Present in a subset of diverse prokaryotes termed diazotrophs, all BNF is catalyzed by the enzyme nitrogenase in a complex, energy-intensive reaction that reduces dinitrogen (N 2 ) into ammonia (NH 3 ), which is subsequently incorporated into cell mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 98 publications
(163 reference statements)
1
9
0
Order By: Relevance
“…Yet, several studies in benthic environments have reported the presence of nif genes, coding for the canonical Mo-nitrogenase, in areas with relatively high bulk levels of ammonium, which have raised questions on the possible contributions of BNF to N input in the presence of NH 4 + and on the spatio-temporal complexity of benthic N cycling [36] . In support of the traditional conceptualization of BNF as a less-preferred N source, recent findings showed clear downregulation of benthic BNF activity in the presence of ammonium [11] , [13] . However, measured NH 4 + thresholds for BNF inhibition in naturally heterogeneous benthic sediments were relatively high (<30 µM NH 4 + , [13] , 0–20 µM NH 4 + , [11] ) as compared to cellular thresholds in liquid culture (<2 µM, [11] ).…”
Section: Introductionmentioning
confidence: 61%
See 4 more Smart Citations
“…Yet, several studies in benthic environments have reported the presence of nif genes, coding for the canonical Mo-nitrogenase, in areas with relatively high bulk levels of ammonium, which have raised questions on the possible contributions of BNF to N input in the presence of NH 4 + and on the spatio-temporal complexity of benthic N cycling [36] . In support of the traditional conceptualization of BNF as a less-preferred N source, recent findings showed clear downregulation of benthic BNF activity in the presence of ammonium [11] , [13] . However, measured NH 4 + thresholds for BNF inhibition in naturally heterogeneous benthic sediments were relatively high (<30 µM NH 4 + , [13] , 0–20 µM NH 4 + , [11] ) as compared to cellular thresholds in liquid culture (<2 µM, [11] ).…”
Section: Introductionmentioning
confidence: 61%
“…In support of the traditional conceptualization of BNF as a less-preferred N source, recent findings showed clear downregulation of benthic BNF activity in the presence of ammonium [11] , [13] . However, measured NH 4 + thresholds for BNF inhibition in naturally heterogeneous benthic sediments were relatively high (<30 µM NH 4 + , [13] , 0–20 µM NH 4 + , [11] ) as compared to cellular thresholds in liquid culture (<2 µM, [11] ). This difference suggests that sediment bio-physical complexity (e.g., nutrient diffusion, remineralization, flow heterogeneity) could significantly obscure our ability to observe “true” sensitivities in various sediment types.…”
Section: Introductionmentioning
confidence: 61%
See 3 more Smart Citations